PENERAPAN KURIKULUM MERDEKA TERHADAP PEMBELAJARAN TEKS CERPEN DI KELAS XI FASE F SMAN 5 PADANG - Salsabila, Kisra; Aprisa Fitri, Laura; Dwi Azzahra, Nadhisya; Zulfahrita Putri, Nadia; Olva Zuve, Farel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Indonesian education system has undergone significant transformation since the implementation of the Independent Curriculum (Curriculum Merdeka) in the 2022/2023 academic year. This curriculum replaces the old, rigid approach with a more flexible, participatory, and student-potential-focused system. In the context of Indonesian language learning, the Independent Curriculum provides space for students to develop creativity, critical thinking, and express ideas through various texts, including short stories. This study aims to describe the initial planning of the Independent Curriculum's application in short story teaching at SMAN 5 Padang, specifically in designing strategies to address common writing difficulties faced by students. The research utilized a descriptive qualitative method, leveraging observation, interviews, and documentation techniques. The focus of the study is directed at the planning of learning methods Problem-Based Learning (PBL), media differentiation, assessment strategies, and the planned use of appreciative communication between teachers and students. The results of this planning study indicate that the implementation strategy emphasizes student-centered learning using the Problem-Based Learning (PBL) model, incorporating media differentiation between video and text, alongside the use of positive communication to motivate students. Providing freedom to choose story themes is planned as an effective strategy for improving motivation and writing quality. Teachers are designed to act as facilitators, not sole directors, using an approach that values students' learning processes. Overall, this planning demonstrates that the Independent Curriculum holds the potential not only to develop better writing skills but also to create an inclusive, creative, and humane learning space for students in the digital age.